2010
DOI: 10.1785/0120090074
|View full text |Cite
|
Sign up to set email alerts
|

Rupture Directivity Characteristics of the 2003 Big Bear Sequence

Abstract: We have developed a forward modeling technique to retrieve rupture characteristics of small earthquakes (3 < M < 5), including rupture propagation direction, fault dimension, and rupture speed. The technique is based on an empirical Green's function (EGF) approach, where we use data from collocated smaller events as Green's functions to study the bigger events. We tend to choose smaller events with similar focal mechanisms for EGFs; however, we show that the events with different focal mechanisms can work equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…This derivation naturally results in the preservation of source time function area as is often assumed in previous studies (Lay & Wallace 1995;Tan & Helmberger 2010), as shown by the red curves relative to blue curve in Fig. 2.…”
Section: Source Time Functions For a Unilaterally Propagating Sourcesupporting
confidence: 57%
See 2 more Smart Citations
“…This derivation naturally results in the preservation of source time function area as is often assumed in previous studies (Lay & Wallace 1995;Tan & Helmberger 2010), as shown by the red curves relative to blue curve in Fig. 2.…”
Section: Source Time Functions For a Unilaterally Propagating Sourcesupporting
confidence: 57%
“…Although there is variability in the manner in which an earthquake ruptures on a fault plane (Wald & Heaton 1994;Beroza 1995;Ide & Takeo 1997;Yue et al 2012;Ye et al 2013), unilateral rupture is generally predominant in a wide range of earthquake magnitudes (McGuire et al 2002;Tan & Helmberger 2010;Kane et al 2013). As unilateral rupture occurs, seismic waves radiated in the direction of rupture could be greatly amplified, and even moderate magnitude earthquakes can sometimes cause serious damage (Huang et al 2011;Kanamori et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The static stress drop is close to the value (~5 bars) from the inversion of GPS data yielded by Ching et al (2011). The 2010 JiaSian earthquake is therefore a low static stress drop event relative to a high rupture velocity (e.g., Tan and Helmberger 2010;Hwang et al 2012). Such a low static stress drop for the JiaSian earthquake lapses from the values for the interplate and intraplate earthquakes (Kanamori and Anderson 1975).…”
Section: Discussionsupporting
confidence: 66%
“…A special feature of the 2010 JiaSian earthquake is a low static stress drop of approximately 5 bars, which was derived from GPS data using an elastic uniform stress drop inversion by Ching et al (2011). Such a low stress drop for the JiaSian earthquake departs from the values (30 -100 bars) for the so-called interplate and intraplate earthquakes (Kanamori and Anderson 1975), but is comparable with a reciprocal relationship between stress drop and rupture velocity (Tan and Helmberger 2010). A low stress drop is therefore relative to a high rupture velocity for the 2010 JiaSian earthquake (Hwang et al 2012).…”
Section: Introductionmentioning
confidence: 96%